Prinsip-prinsip Human Relations dalam Pelaksanaan Komunikasi Organisasi di Kementerian Komunikasi dan Informatika - Denia Prameswari Putri; Donie Kadewandana (Fakultas Ilmu Komunikasi Universitas Pancasila, 2018)
Some organizations have not realized the importance of attention to employees in the organization. It is then important to do human relations that can be one way in the fulfillment of one of the needs of the needs of employees. Human relations is discussed by analyzing the principles of human relations in the implementation of organizational communication at the Bureau of Public Relations of the Ministry of Communications and Information Technology (Kemkominfo). Kemkominfo that has public relations in it, also participate in implementing human relations because one of the public relations function is to build good relationships including the internal public. Thus the purpose of this study to analyze the principles of human relations in the implementation of organizational communication on the Bureau of Public Relations Kemkominfo. This research uses postpositivist paradigm, qualitative approach, descriptive research type, individual analytical unit, data collecting technique using semistructure interview, observation and documentation. The results of verified data in the field that human relations activities on the Public Relations Bureau of Kemkominfo using seven of the eight principles of human relations Keith Davis. One principle that has not been used is the principle of mutual acceptance. Public Relations Kemkominfo in implementing human relations also have not used one principle of communication openness. However, in the implementation of organizational communication that also involves the elements of communication, the Public Relations Bureau has used the three flow of information within the organization and dominant is horizontal communication.